Qualitative Research Methods and Evidential Reasoning. Issue 5 (September 2019) - Matta, Corrado
This article discusses the concept of evidential reasoning in the context of qualitative research methods in the social sciences. A conceptualization of qualitative evidential reasoning is proposed. This conceptualization is based on the analysis of an example of qualitative methods applied to the study of music education. I argue that this conceptualization identifies specific and nontrivial conditions for qualitative evidential reasoning and, at the same time, supports the claim that there is no essential methodological separation regarding evidence between quantitative and qualitative methods.